Graduate transitions in Africa: Understanding strategies of livelihood generation for universities to better support students (Journal of Student Affairs in Africa, 2023)
Graduate transitions and pathways do not naturally involve moving smoothly or sequentiallyfrom education into the world of work. Instead university graduates move through employment,entrepreneurship, unemployment and continued further education as they generate livelihoods. ForAfrican universities to be student-centred, with a focus on student development and success, thenature of these livelihood pathways must be examined in order to provide appropriate and relevanttraining and transition support. This article uses quantitative and qualitative data from Africangraduates who received a scholarship to complete their degrees at 21 universities (nine in Africa and12 from other countries). Their post-graduation pathways are mapped and explored to determinehow graduates generate livelihoods. The findings show that a minority of African graduates movesmoothly from education into employment, and that for the majority, pathways are multidimensionaland complex. While some move into the world of work with ease, most develop portfolios of income.By developing initiatives based on these findings, universities can help graduates navigate thechallenges of income diversification, provide them with the necessary skills and resources, and fostera supportive ecosystem that encourages entrepreneurial thinking and diversified career paths.